Quality Culture Model in Improving Development Madrasah Universitas Islam Negeri Jakarta Indonesia and Ma'had Al Ulum Addiniyah Thailand - Masyitoh, Masyitoh; Bahar, Herwina; Suryadi, Ahmad; Bahri, Saiful; Nisoh, Anan; Niwae, Yahaya; Sama-alee, Abdulrahman; Sundi, Venni Herli (International Journal of Contemporary Studies in Education, 2023)
The purpose of this research is to compare the quality culture of Islamic Education Institutions in Indonesia and in Thailand, specifically the UIN Jakarta Development Madrasah and Ma'had Al-Ulum Addiniyah Pohontanjong Narathiwat with the eight National Education Standards (SPN). This research method is descriptive-comparative with a qualitative approach. The results showed the characteristics of the quality culture of each Islamic Education Institution in Indonesia and in Thailand, in addition to the similarities in the management of these Educational Institutions such as, the characteristics of the quality culture of the UIN Jakarta Development Madrasah and the characteristics of the quality culture of Ma "had Al-Ulum Addiniyah Pohontanjong Narathiwat in Thailand. The similarity of the quality culture of the two institutions refers to the national curriculum set by the respective governments by strengthening the local curriculum according to the needs of each institution. The difference in the governance of these two institutions, shown in the UIN Jakarta Development Madrasah is managed by a foundation that is responsible to the State University, while Ma "had Al-Ulum Addiniyah Pohontanjong Narathiwat is managed by local community leaders. The development of a culture of quality in each Islamic educational institution is highly dependent on the leadership of the madrasah/ma "had as the "central" driver in managing the learning process and quality institutions that can improve the quality of education that is universal and competitive at the international level.